1988
DOI: 10.1111/j.1365-2389.1988.tb01235.x
|View full text |Cite
|
Sign up to set email alerts
|

A model of solid‐solution interactions in acid organic soils, based on the complexation properties of humic substances

Abstract: SUMMARY CHAOS (Complexation by Humic Acids in Organic Soils) is a quantitative chemical model of organic soils that incorporates complexation by the functional groups of humic substances and non‐specific ion‐exchange reactions. The two types of interaction are linked by the net humic charge, Z, which depends on the extents of proton and metal complexation, and which in turn determines ionic concentrations in the diffuse part of the electrical double layer, by a Donnan equilibrium. CHAOS was found to account sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(86 citation statements)
references
References 13 publications
4
80
0
2
Order By: Relevance
“…Previous studies (e.g. Krug and Frink, 1983;Tipping and Hurley, 1988) have suggested an inverse link between mineral acid inputs and the leaching of organic acidity (and hence DOC) to runoff. It is thus possible that increased DOC concentrations in the UK represent a response to reductions in soil and stream acidity over the last 12 years.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (e.g. Krug and Frink, 1983;Tipping and Hurley, 1988) have suggested an inverse link between mineral acid inputs and the leaching of organic acidity (and hence DOC) to runoff. It is thus possible that increased DOC concentrations in the UK represent a response to reductions in soil and stream acidity over the last 12 years.…”
Section: Discussionmentioning
confidence: 99%
“…A key factor in the release of DOM is the net electrical charge ( Tipping and Hurley, 1988) which is a general property of polyelectrolytes. Hence, the solid organic matter must be altered in terms of an increasing net electrical charge to be released into soil solution.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, factors such as climatic variability and longterm changes in pollutant deposition can dominate variations in water quality (Neal et al, 2004a, b and c) In common with many upland catchments across the UK , DOC concentrations have increased in both the moorland and forest streams over the last 20 years. This may be associated with increasing mobilisation of organic acids in response to a decrease in mineral acid inputs (Krug and Frink, 1983;Tipping and Hurley, 1988). However, it has been suggested that climatic controls are more important (Freeman et al, 2001), given that increases in DOC are observed at sites which have received relatively little acid deposition (Worral et al, in press).…”
Section: Discussionmentioning
confidence: 99%